Competitiveness of Indonesian Cocoa in Major Export Destination Countries Using Porter’s Diamond Model Approach - Risqi Firdaus Setiawan; Teguh Soedarto; Hamidah Hendrarini; Mubarokah Mubarokah (The University of Lampung, 2025)
Indonesia is one of the world’s leading cocoa producers, yet its contribution to global value-added cocoa exports remains relatively low. This structural gap highlights the need to evaluate not only production capacity but also the competitiveness of Indonesian cocoa in international markets. This study aims to evaluate the competitiveness of Indonesian cocoa exports in four main destination countries: India, China, Malaysia, and the Philippines. Data sources were obtained from UM Comtrade, ITC Trademap, International Cocoa Organization (ICCO), and BPS. The analysis was conducted by combining methods of the Revealed Comparative Advantage, Export Competitiveness Index, and the Porter's Diamond Model. The results show that Indonesia still has a comparative and competitive advantage in several markets, especially India. The average RCA value was 10.41 in Malaysia, 9.42 (China), 5.40 (India), and 3.97 (the Philippines). Meanwhile, the ECI value is greater than one, namely 1.21 (India), 1.09 (China), 1.08 (Malaysia), and 1.05 (the Philippines). These advantages, however, are volatile and highly dependent on natural resource factors. Weak domestic demand, inconsistent quality standards, limited downstream industry capacity, and fragmented policy coordination remain key structural challenges. This research emphasizes that strengthening competitiveness not only requires the maintenance of comparative advantage, but also its transformation into a sustainable competitive advantage through institutional reform, cross-sector policy integration, and value-added product innovation.